IMPLEMENTASI PEMBERDAYAAN USAHA EKONOMI MIKRO KECIL DAN MENENGAH (UMKM) - Goso Goso; Samsul Bachri (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2015)
To speed up economy restoration with brace development basement sustainability and with justice based on in democracy economy system. Done to pass development at economy area with development at Natural Resources (SDA) and environment. Make use wealth SDA without neglecting principles sustainability and environment preservation. Effort development micro intermediate little can give big contribution towards bational economy restoration process so that necessary more be payed because, by using technics analysis diskriptif, technics factor analysis, and doubled linear regression is found factors that determine development success UMKM among others Human Resource (SDM), capitalization, engine and device, effort management, marketing, basic commodity availability, and information so that can do global access. Bear mission creats generalization chances work and try to preserve culture, and support to export national. Technicaly survey existence UMKM at unlucky city to effort areas classification arrangement, effort stratification, and troubleshoot identification, need, and the potential, with influential factors towards the development. Furthermore evaluation towards that got and database that made based on the effort area classification operationally permanent refer in construction masterplan and small industry development and intermediate with pay attention potential region.